Development, microstructure and mechanical characterisation of nickel-based ceramic reinforced metal matrix composites manufactured by laser powder bed fusion - Mwambe, Polline (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2025.